Resolving the paradox of randomised controlled trials and observational studies comparing multi-vessel angioplasty and culprit only angioplasty at the time of STEMI. (1st November 2016) - Ahmad, Yousif; Cook, Christopher; Shun-Shin, Matthew; Balu, Ashwin; Keene, Daniel; Nijjer, Sukhjinder; Petraco, Ricardo; Baker, Christopher S.; Malik, Iqbal S.; Bellamy, Michael F.; Sethi, Amarjit; Mikhail, Ghada W.; et al.
Abstract: Background: Patients presenting with ST-elevation myocardial infarction commonly have multi-vessel coronary artery disease. After the culprit artery is treated, the optimal treatment strategy for the residual disease is not yet defined. Large observational studies suggest that treatment of residual disease should be deferred but smaller randomised controlled trials (RCTs) suggest multi-vessel primary percutaneous coronary intervention (MV-PPCI) at the time of STEMI is safe. We examine if allocation bias of high-risk patients could explain the conflicting results between observational studies and RCTs and aim to resolve the paradox between the two. Methods: A meta-analysis of registries comparing culprit-only PPCI to MV-PPCI was performed. We then determined if high-risk patients were more likely to be allocated to MV-PPCI. A meta-regression was performed to determine if any allocation bias of high-risk patients could explain the difference in outcomes between therapies. Results: 47, 717 patients (19 studies) were eligible. MV-PPCI had higher mortality than culprit-only PPCI (OR 1.59, 95% CI 1.12 to 2.24, p = 0.03). However, higher risk patients were more likely to be allocated to MV-PPCI (OR 1.45, 95% CI 1.18 to 1.78, p = 0.0005). When this was accounted for, there was no difference in mortality between culprit-only PPCI and MV-PPCI (OR 0.99, 95% CI 0.69 to 1.41, p = 0.94). Discussion: Clinicians preferentially allocate higher-risk patients to MV-PPCI at the time of STEMI, resulting in observational studies reporting higher mortality with this strategy. When this is accounted for, these large observational studies in 'real world' patients support the conclusion of the smaller RCTs in the field: MV-PPCI has equivalent mortality to a culprit-only approach.